Effect of Chronic Stress Present in Fibroblasts Derived from Patients with a Sporadic Form of AD on Mitochondrial Function and Mitochondrial Turnover - Karolina Drabik; Dominika Malińska; Karolina Piecyk; Grażyna Dębska-Vielhaber; Stefan Vielhaber; Jerzy Duszyński; Joanna Szczepanowska (MDPI AG, 2021)
Although the sporadic form of Alzheimer's disease (AD) is the prevalent form, the cellular events underlying the disease pathogenesis have not been fully characterized. Accumulating evidence points to mitochondrial dysfunction as one of the events responsible for AD progression. We investigated mitochondrial function in fibroblasts collected from patients diagnosed with the sporadic form of AD (sAD), placing a particular focus on mitochondrial turnover. We measured mitochondrial biogenesis and autophagic clearance, and evaluated the presence of bioenergetic stress in sAD cells. The mitochondrial turnover was clearly lower in the fibroblasts from sAD patients than in the fibroblasts from the control subjects, and the levels of many proteins regulating mitochondrial biogenesis, autophagy and mitophagy were decreased in patient cells. Additionally, the sAD fibroblasts had slightly higher mitochondrial superoxide levels and impaired antioxidant defense. Mitochondrial turnover undergoes feedback regulation through mitochondrial retrograde signaling, which is responsible for the maintenance of optimal mitochondrial functioning, and mitochondria-derived ROS participate as signaling molecules in this process. Our results showed that in sAD patients cells, there is a shift in the balance of mitochondrial function, possibly in response to the presence of cellular stress related to disease development.